ANALISIS PERBANDINGAN EFISIENSI DAYA PANEL SURYA 200 WP DENGAN TURBIN ANGIN SUMBU VERTIKAL 200 WATT - Lela Nurpulaela; Dian Budhi Santoso; Lucky Gunawan (Aisyah Journal Of Informatics and Electrical Engineering (A.J.I.E.E), 2023)
Electrical energy is currently one of the main needs needed by humans to carry out daily activities. The process of generating electrical energy is carried out through the transformation of various energy sources, either using conventional energy sources or using renewable energy. One of Renewable energy is being developed is wind power and solar power. However, in the application of these two energy sources there are still deficiency, namely the value of energy conversion efficiency is still small and is very much influenced by environmental conditions such as the value of solar irradiation and wind speed, this can affect to energy production the electricity generated. The purpose of this research is to carry out a comparative analysis of the power efficiency produced by a 200 Wp solar panel with a 200 watt vertical axis wind turbine. The test was carried out in Karawang Regency. The results of this study show that solar panels have a higher efficiency value than wind turbines with an average solar panel efficiency value of 5.12% and an average wind turbine efficiency value of 2.05%. The results of wind turbine efficiency tend to be small because the wind that blows is not always stable and only lasts a few moments.